Power system security enhancement by OPF with phase shifter. - Momoh, J.A (IEEE Transactions on power systems)
This paper presents an integrated optimal power flow (OPF) with phase shifter approach to enhance power system security. The general OPF calculations are hourly based and the control variables of OPF are continuous. However, the calculations of phase shifter are daily based, and the variables related to phase shifter are discrete. Therefore, the general OPF cannot be directly used to solve this problem. The paper develops the rule-based OPF with phase shifter scheme to bridge the problems. In order to effectively alleviate the line overloads, the ranking of phase shifter locations is conducted based on contingency analysis and sensitivity analysis. The best phase shifter sites are identified and selected into a rule-based system accordingly. The handshaking procedure between the adjustment of the selected phase shifters and OPF calculation is proposed using a rule-based method. The hourly-based OPF problem is solved by the extended quadratic interior point method. The IEEE 30-bus system is used to test the proposed scheme